Changes in abundance and breeding output of Greylag Geese Anser anser breeding in southern Sweden - Nilsson, Leif (Wildfowl, 2018)
Neck-banded Greylag Geese Anser anser from a population breeding in southwest Scania, southern Sweden, were studied to assess changes in the breeding population and breeding performance during 1984–2013. The population increased ten-fold during this period, only to decrease again in the later years of the study. Greylag Geese arrived on the breeding grounds about 3–4 weeks earlier by 2007–2009 compared to the 1980s, probably an effect of wintering further north closer to the breeding areas in more recent years. Mean hatch date did not advance significantly over the same period. The proportion of breeding Greylag Geese that produced a brood of small young decreased during the study. On the other hand, the mean brood size at hatching for those succeeding in producing a brood, and the survival of young to fledging amongst marked families, showed no significant trends.